Mikrovoltový T-ware alternas: je přínosný pro indikaci ICD? - Costantini, Otto; Hohnloser, S. H; Kirk, M. M; Lerman, B. B; Baker, J. H; Sethuraman, B; Dettmer, M. M; Rosenbaum, D. S (Clinical Cardiology Alert, 2009)
Because risk stratification with electrophysiological study (EPS) improves efficiency but is invasive, we sought to determine whether noninvasive microvolt T-wave alternans (MTWA) testing could identify patients who benefit from implantable cardioverter-defibrillators (ICDs) as well as EPS. BACKGROUND: Prevention of sudden cardiac death on the basis of left ventricular ejection fraction (LVEF) alone is inefficient, because most ICDs never deliver therapy. METHODS: The ABCD (Alternans Before Cardioverter Defibrillator) trial is a multicenter prospective study that enrolled patients with ischemic cardiomyopathy (LVEF < or =0.40) and nonsustained ventricular tachycardia. All patients underwent MTWA and EPS. ICDs were mandated if either test was positive. RESULTS: Of 566 patients followed for a median of 1.9 years, 39 (7.5%) met the primary end point of appropriate ICD discharge or sudden death at 1 year. As hypothesized, primary analysis showed that MTWA achieved 1-year positive (9%) and negative (95%) predictive values that were comparable to EPS (11% and 95%, respectively). In addition, secondary analysis showed that at the pre-specified 1-year end point, event rates were significantly higher in patients with both a positive MTWA-directed strategy (hazard ratio: 2.1, p = 0.03) and a positive EPS-directed strategy (hazard ratio: 2.4, p = 0.007). Moreover, the event rate in patients with both negative MTWA test and EPS was lower than in those with 2 positive tests (2% vs. 12%; p = 0.017). CONCLUSIONS: The ABCD study is the first trial to use MTWA to guide prophylactic ICD insertion. Risk stratification strategies using noninvasive MTWA versus invasive EPS are comparable at 1 year and complementary when applied in combination. Strategies employing MTWA, EPS, or both might identify subsets of patients least likely to benefit from ICD insertion. (Study to Compare TWA Test and EPS Test for Predicting Patients at Risk for Life-Threatening Heart Rhythms [ABCD Study]; NCT00187291).
Keywords: kardiomyopatie; srdeční elektrofyziologie; Aged; Treatment Outcome; hodnocení rizik; lidé středního věku; senioři; lidé; komorová tachykardie; Cardiomyopathies; Middle Aged; Death, Sudden, Cardiac; Tachycardia, Ventricular; Electrocardiography; Female; Risk Assessment; výsledek terapie; financování organizované; Male; ženské pohlaví; Cardiac Electrophysiology; Humans; mužské pohlaví; elektrokardiografie; ischemická choroba srdeční; Defibrillators, Implantable; Financing, Organized; Myocardial Ischemia; defibrilátory implantabilní; náhlá srdeční smrt